A közoktatási intézményhálózat és a helyi társadalom - Forray R., Katalin (Tér és Társadalom, 1987)
The proportion of Hungarian population without completed elementary school is still too large. Some of these people could still finish elementary school within the frameworks of adult education. In order to reach this aim it is necessary to know the spatial distribution of people who have not completed elementary education as well as the location of schools. The present paper classifies and analyses the settlements according to the public school facilities available locally. Considering some important indicators relating to local communities, namely: the educational level of the population, the employment and the age structure of the inhabitants, two extremes can be distinguished: settlements with no school whatsoever are placed at the negative end of the scale while those with alt kinds of public schools are at the positive extreme. The subdivision of settlements which only have some elements of public school facilities highlights the fact that the presence of a kindergarten is a better indicator of the quality of local community than that of schools. At present, however, the kindergarten cannot provide organized frameworks for adult education. Unfortunately, the undereducated population is concentrated and, according to statistics on schooling, it is reproduced in areas where the established institutions of organized education are missing or can only partly be available. When elaborating the possible forms of support in this field it should be kept in mind that the population in these settlements is rather unstable.